Identifikasi Faktor Stigma Pasien Penyakit Virus Corona (COVID-19) yang Terkonfirmasi di Indonesia - Agus, Alamsyah; Alfrojems, Alfrojems; Ramdani, Jaka; Matasik, Delfania; Dharmika, Ida Ayu Gde Pradnyawidari (UI Scholars Hub, 2022)
Background. The COVID-19 pandemic has emerged as a disaster and is a global health crisis for human beings. The pandemic is not only haunted by tragedies of national fatality rate was about 5% of the sufferers, but also stigmatized by the community. Aim. This study aims to assess the factors of the stigma associated with the COVID-19 pandemic and its impact among patients with confirmed COVID-19 in Indonesia. Method. This case study was conducted in 2020 by collecting information from primary sources that include interviews virtually with 4 COVID-19 survivors in Indonesia. Result. The result of this study shows that factors of stigma consist of three factors which consist of the disease is new and much information remains unknown; we are often afraid of the unknown; and the fear of the unknown can easily be associated with ‘others’. Conclusion. In the beginning of the COVID-19 pandemic, people in Indonesia did not clearly understand the COVID-19 epidemic, including its transmission, management, and how to avoid it. This misunderstanding can lead to stigmatization and possibly extend the pandemic and the length of large-scale social restrictions.